2021
DOI: 10.1002/alr.22897
|View full text |Cite
|
Sign up to set email alerts
|

Odorant metabolism of the olfactory cleft mucus in idiopathic olfactory impairment patients and healthy volunteers

Abstract: Background: It remains unclear whether the metabolic activity of nasal mucus in the olfactory and respiratory areas is different. Moreover, age-and olfactionrelated changes may affect metabolism.Methods: Hexanal, octanal, and 2-methylbutanal were selected for in vitro metabolism analysis and compared between the olfactory cleft and respiratory mucus of participants < 50-year-old with normal olfaction using gas chromatography mass spectrometry. The metabolic activity of hexanal in the olfactory cleft mucus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 33 publications
(49 reference statements)
2
24
0
9
Order By: Relevance
“…More recently, the same group investigated the conversion of aldehydes to their corresponding alcohols in the human mucus obtained from the olfactory cleft or respiratory tissue, the latter showing a lower metabolism for octanal, hexanal, and 2‐methybutanal. Additionally, hexanal mucus metabolism was significantly lower in participants with idiopathic olfactory impairment [66] . Takaoka et al.…”
Section: Odorant Metabolism In the Nasal And Oral Cavities The Lrt An...mentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, the same group investigated the conversion of aldehydes to their corresponding alcohols in the human mucus obtained from the olfactory cleft or respiratory tissue, the latter showing a lower metabolism for octanal, hexanal, and 2‐methybutanal. Additionally, hexanal mucus metabolism was significantly lower in participants with idiopathic olfactory impairment [66] . Takaoka et al.…”
Section: Odorant Metabolism In the Nasal And Oral Cavities The Lrt An...mentioning
confidence: 96%
“…Additionally, hexanal mucus metabolism was significantly lower in participants with idiopathic olfactory impairment. [66] Takaoka et al showed the enzymatically driven oxidation of aldehydes to their corresponding carboxylic acid, and the involvement of aldehyde oxidases in mouse. Since AOX are also found in in the human OE this might give a starting point for further investigations.…”
Section: Odorant Metabolism In the Nasal And Oral Cavities The Lrt An...mentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) [66] zeigten kürzlich, dass die Geruchsstoffe Hexanal, Octanal und 2‐Methylbutanal in In‐vitro ‐ Experimenten durch menschlichen Mukus verstoffwechselt werden. Der Hexanal‐Stoffwechsel war hierbei bei Versuchspersonen mit idiopathischer Beeinträchtigung deutlich geringer [66] . Krankheits‐ und Verletzungszustände sowie Einflüsse durch entsprechende Medikamente sind daher weitere Faktoren, die bei der Untersuchung individueller Unterschiede im Geruchsstoffmetabolismus berücksichtigt werden sollten [66] .…”
Section: Ausblick: Weitere Forschung Und Anwendung Auf Dem Gebiet Des...unclassified
“…Ein weiterer Aspekt betrifft die Entwicklung von Diagnoseinstrumenten: Das Verständnis des Geruchsstoffmetabolismus bei gesunden und erkrankten Personen könnte zur Entwicklung nicht-invasiver Screening-Methoden für eine Vielzahl von Krankheiten beitragen. Prominente Marker wie Aceton bei Diabetes [116] konnten als Indikatoren für andere Krankheiten wie Krebs oder Parkinson [117] [66] zeigten kürzlich, dass die Geruchsstoffe Hexanal, Octanal und 2-Methylbutanal in Invitro-Experimenten durch menschlichen Mukus verstoffwechselt werden. Der Hexanal-Stoffwechsel war hierbei bei Versuchspersonen mit idiopathischer Beeinträchtigung deutlich geringer.…”
Section: Ausblick: Weitere Forschung Und Anwendung Auf Dem Gebiet Des...unclassified